Effect of wheat gluten addition on the texture, surface tackiness, protein structure, and sensory properties of frozen cooked noodles. (1st May 2022) - Wang, Yuan-Hui; Zhang, Ya-Ru; Yang, Yue-Ying; Shen, Jin-Qi; Zhang, Qiu-Mei; Zhang, Guo-Zhi
Abstract: Frozen cooked noodles (FCNs) were prepared with different levels (0, 1%, 3% and 5%) of gluten addition, and the effect of gluten on quality of FCNs was investigated. Cooking properties analysis showed that water absorption ratio and cooking loss of FCNs decreased at first and then increased with the increase of gluten addition. Compared to FCNs with 1% and 5% gluten additions, recooked FCNs with 3% gluten addition had a similar texture property to control sample, and they had the highest tensile force and distance, and the lowest surface tackiness. Meanwhile, the recooked FCNs (3% gluten addition) had smaller pores, denser and more complex gluten network, and their force and elasticity during chewing were the best in sensory evaluation. Low-field 1H nuclear magnetic resonance showed that the lowest T 21 (0.11 ms) and T 23 (51.11 ms) were found in the recooked FCNs (3% gluten addition). Furthermore, the α-helix of samples increased while the β-sheet and random coil decreased, the glutenin macropolymer content of recooked FCNs increased at first and then decreased with adding gluten. These results indicated that the recooked FCNs (3% gluten addition) had a lower surface tackiness, higher sensory scores, and better quality. Highlights: Wheat gluten was effective in changing the surface tackiness in recooked frozen cooked noodles. Wheat gluten could strengthen protein network and tightly wrap starch granules. Wheat gluten addition formed a denser and more continuous protein-starch network. Wheat gluten promoted the transformation of protein secondary structure. Wheat gluten improved the cooking and texture quality of recooked frozen cooked noodles.